In vitro antagonistic activity of Lactobacillus casei against Helicobacter pylori - Enany,Shymaa (2015)
Helicobacter pylori is one of the most common causes of chronic infections in humans. Curing H. pylori infection is difficult because of the habitat of the organism below the mucus adherent layer of gastric mucosa. Lactobacilli are known as acid-resistant bacteria and can remain in stomach for a long time than any other organism, we aimed in this study to examine the efficacy of Lactobacillus casei as a probiotic against H. pylori in humans. Particularly, L. casei was opted as it is considered to be one of the widely used probiotics in dairy products. One hundred and seven strains of H. pylori were isolated from dyspeptic patients and were tested for their antibiotic susceptibility to metronidazole (MTZ), clarithromycin (CLR), tetracycline (TET), and amoxicillin (AMX) by the disc diffusion method. The strains were examined for their susceptibility toward L. casei - present in fermented milk products - by well diffusion method. It was found that 74.7% strains were resistant to MTZ; 1.8% to MTZ, TET, and CLR; 3.7% to MTZ and CLR; 4.6% to MTZ and TET; and 0.9% were resistant to MTZ, TET, and AMX. The antibacterial activity of L. casei against H. pylori was determined on all the tested H. pylori isolates including antibiotic resistant strains with different patterns. Our study proposed the use of probiotics for the treatment of H. pylori infection as an effective approach.